Interfacial failure of circular or tubular hybrid bonded joints: A theoretical description. (February 2022) - Biscaia, Hugo C.; Carvalho, Marta S.; Martins, Ana P.; Micaelo, Rui
Highlights: Tubular or circular hybrid bonded joints with a double butt lap configuration are analysed. An analytical axisymmetric formulation to model the interfacial failure of hybrid joints is proposed. The proposed analytical model is validated by using a commercial finite element code. Both approaches led to the identification of three different interfacial failure scenarios. A total of 48 different cases were simulated and studied thoroughly. Abstract: In different industries, the bonding technique has gained several advances in recent years. However, due to the specificity of each industry, the bonded joints may present different configurations. For instance, in the case of metallic truss bridges, the use of Carbon Fibre Reinforced Polymers (CFRP) bonded on the steel surface members may require circular or even tubular transitions between these materials. Although the bonded transitions between a metal and a composite material have been deeply studied with flat surfaces the information on circular or tubular hybrid bonded joints is still scarce. Therefore, the present study aims to mitigate some of this lack of knowledge by proposing an analytical solution able to describe the interfacial debonding process between a circular or tubular bonded transition between two materials. The proposed model also aims to simulate the interfacial debonding of double butt (or stepped) lap joints. Under these circumstances, a bilinear local adhesive model is adopted which required the quantification of the elastic and the softened stiffnesses as well as the pure Mode II fracture energy. The Finite Element Method (FEM) is used for the validation of the proposed model. The behaviour of the adhesive joint between materials is numerically modelled through the Cohesive Zone Modelling (CZM) in which the same bilinear shape used in the analytical solutions is adopted. Different situations were analyzed thoroughly and the numerical simulations tracked very closely the analytical results obtained from the proposed closed-form solutions.